2022
DOI: 10.1080/15226514.2022.2117790
|View full text |Cite
|
Sign up to set email alerts
|

Supportive effect of naringenin on NaCl-induced toxicity in Carthamus tinctorius seedlings

Abstract: BackgroundThe exogenous application of priming molecules to plants helps them to develop tolerance against salinity stress. In the present study, we used exogenous naringenin (0.5 mM) pretreatment before the stress in sa ower seedlings under 25 mM NaCl to elucidate the role of naringenin to alleviate oxidative conditions associated with salinity complications. ResultsOur results showed biomass, leaf relative water content, chlorophyll content, K + content, and K + /Na + ratio were negatively affected by 25 mM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 55 publications
2
5
0
Order By: Relevance
“…While in the cells of the Moringa oleifera plant this trend was significantly less pronounced, herewith in quinoa sprouts there was no statistically significant difference between the experimental and control variants [ 30 , 46 ]. There are data confirming the increase in the accumulation of PCs in Carthamus tinctorius and Vigna radiata seedlings in the presence of Nar, while in the first case this indicator increased almost two-fold [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…While in the cells of the Moringa oleifera plant this trend was significantly less pronounced, herewith in quinoa sprouts there was no statistically significant difference between the experimental and control variants [ 30 , 46 ]. There are data confirming the increase in the accumulation of PCs in Carthamus tinctorius and Vigna radiata seedlings in the presence of Nar, while in the first case this indicator increased almost two-fold [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 78%
“…The described effect of Nar is confirmed by the data obtained in the work of Sharma et al where a similar trend was noted [ 27 ]. At the same time, there was shown no change in water content using the example of Carthamus tinctorius seedlings in the presence of the indicated above precursor [ 28 ]. It is worth noting that for Phe, a similarity to our data effect was noted for the Vitex agnus castus shoot cultures and Cicer arietinum seedlings [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 It has recently been demonstrated that Nar contributes to enhanced plant growth, increased osmotic regulation, and increased vegetative development, biochemical accumulation, and protein bioavailability. 14 Phenolic-derived compounds may have various synergistic or antagonistic effects on plants when combined, [15][16][17] but these effects are not currently well known. Therefore, the aim of this study is to investigate the potential synergistic, neutral, and antagonistic effects of exogenous RA and Nar application on the metabolic processes of L. sativum, aiming to enhance our understanding of how these compounds influence the overall bioactive compounds in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Naringenin (4′,5,7‐trihydroxyflavanone) (Nar) is another phenolic with antioxidant, free radical scavenger, anti‐inflammatory, immune system modulation properties, widely distributed in citrus fruits 13 . It has recently been demonstrated that Nar contributes to enhanced plant growth, increased osmotic regulation, and increased vegetative development, biochemical accumulation, and protein bioavailability 14 …”
Section: Introductionmentioning
confidence: 99%